Should the 4 big replace the big 4? An examination of audit quality using internal audit - Singh, Harjinder; Newby, R.; Singh, Inderpal (Virtus Interpress, 2012)
Prior research has linked audit quality with large audit firms. Consequently, a dichotomous variable, Big N/non-Big N has traditionally proxied for audit quality. Applying a different measure of audit quality than audit fee, this study investigates whether a single dummy variable for Big N is an appropriate proxy for audit quality in explaining differences in the existence of clients' internal audit (IA) function. Results indicate that the existence of clients' IA function is not consistent among Big 4 firms. This has important research implications for the universal use of a Big N dummy variable as a measure for audit quality.